Smartphone display size can cause distortions in perceptual estimates of size. (November 2021) - Sanchez, Christopher A.; Read, Tyler; Crawford, Amanda
Abstract: Everyday we consume massive amounts of visual information on mobile devices like smartphones. However, are there consequences for viewing information on these devices? In 2 experiments, participants viewed several target objects on two differently sized virtual smartphone displays, and then made a judgment of the size of each target item. Results from both experiments confirm that smartphone display size does impact user perceptions of size, such that larger displays cause users to significantly underestimate the size of objects. This effect held when target items were presented alone, or concurrently with a non-target referent. This is the first study to confirm such an effect and suggests that the size of a smartphone display can negatively influence the accuracy of users' visual perception. Thus, beyond aesthetics or cost, it must be realized that the choice of device might have additional perceptual consequences for consumers. Highlights: Previous work has shown that screen size does impact user attitudes. In this study users consistently underestimated target size on mobile devices. Size estimations when judged on the smaller screen device were more accurate. Including consistently sized referents reduced, but did not eliminate, this effect. This suggests that larger mobile screens can reduce size perception accuracy.